2019
DOI: 10.18280/i2m.180310
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Measurement of Moisture Sorption Isotherms and Isosteric Heat of Palm Hearts (Jomare) Harvested in the Algerian Sahara

Abstract: Mastering the process of drying the palm heart (Jomare) requires knowing their isothermal sorption. The purpose of this work is the experimental determination of the palm heart sorption isotherms. the gravemitric method of saturated saline solutions is used at three different temperatures (40, 50 and 60 °C) with a water activity extending from 0.067 to 0.85. The equilibrium was obtained after about 10 days. Four mathematical models have been used (LANGMUIR, GAB, modified BET and Peleg) to model and predict hyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The desorption isosteres for tomato are illustrated in The evaluation parameters of the empirical equation with the Levenberg-Marquardt method was effected using the Nonlinear regression , the obtained results were in agreement to other works such as Tsami et al [1] applied for other food product Figure 6 and 7, where we notice that the increase in net desorption heat is compatible with the increases of the degree dehydration as the degree of dehydration increases which is relating to existence highly active polar sites in the product that are been covered by water molecule forming the molecular layer [2,24].…”
Section: Isosteric Sorption Heats Determinationsupporting
confidence: 90%
See 1 more Smart Citation
“…The desorption isosteres for tomato are illustrated in The evaluation parameters of the empirical equation with the Levenberg-Marquardt method was effected using the Nonlinear regression , the obtained results were in agreement to other works such as Tsami et al [1] applied for other food product Figure 6 and 7, where we notice that the increase in net desorption heat is compatible with the increases of the degree dehydration as the degree of dehydration increases which is relating to existence highly active polar sites in the product that are been covered by water molecule forming the molecular layer [2,24].…”
Section: Isosteric Sorption Heats Determinationsupporting
confidence: 90%
“…It is the most consumed cooking ingredient in the world after the potato. It is cultivated in almost all latitudes, covering an area of about 3 million hectares, which represents nearly one-third of the world's surface devoted to vegetables [1,2]. Seasonal post-harvest losses of fruits and vegetables are rich in the tropics because of the warmth of the environment and moisture levels [3].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many authors have reported studies related to its techno-functional properties, potential agroindustrial uses and consumption trends (Lamothe et al, 2015;Lopera-Cardona et al, 2016;Guardianelli et al, 2019;Thakur et al, 2019;Nasirpour-Tabrizi et al, 2020). Biological properties have been studied in relation to protein isolate and proteinprotein interactions, given the characteristics of quinoa reserve proteins (Haros and Wronkowska, 2016;Gürbüz et al, 2018;Dakhili et al, 2019;Larbi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is from these sorption curves that we can determine the final product water content, so as to ensure the physicochemical and microbiological stability during the storage, in addition the product shelf life can be predicted [1][2][3][4][5][6]. studies on sorption isotherms are carried out by mathematical modeling, eight mathematical models (in the literature) empirical and semi-empirical based on more or less physical bases [7][8][9][10], describing the correlation of water content with balance with the water activity of the products. among these models: GAB [11], modified BET [12], Henderson-Thompson [13], modified Halsey [14], modified Oswin [15], Peleg [16].…”
Section: Introductionmentioning
confidence: 99%